Killer reunion - McKevett, G. A. (New York, New York : Kensington Books, 2016)
Triumphantly attending her twenty-fifth high school reunion with her handsome husband, Savannah confronts her nasty former nemesis and is forced to clear her name when the woman is found murdered amid rumors about another suspicious death.
Keywords: Reid, Savannah (Fictitious character) -- Fiction; Women private investigators -- Fiction; Class reunions -- Fiction; Murder -- Fiction; Mystery fiction